The transforming power of science - Parker, Ivan Bryan (My University, 1892)
Introduction: The prerogative of man is to ask for reasons for what he is enjoined to do or believe. The brute does not ask for reasons, the savage, the child and the lowest class of operative work men may not, but a well-developed human being has a dignity about him with which mere blind obedience and unreasoning assent all felt to be inconsistent. We feel it as much our duty to investigate national as well as state affairs, the unnatural as well as the natural, metaphysics as well as physics. Justice, right, duty, and truth should be impressed from the babe, nestling in its mother’s arms, until the old man, sworn crowned, extends his hand with a smile to death. And these have been the missing of science ever since progress was born of discontent, and these are the missions now as it rocks progress in the cradle of doubt and nurtures it by the food of truth.
Citation: Parker, Ivan Bryan. The transforming power of science. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Science; Progress; Nature; Nurture; Power; Theses; Manuscripts (documents)